Hand detection for computer graphical user interface control - Aiman Syakir, Sobki (2016)
Computer has become a vital part in humans’ lives as it has become difficult to work without a computer. Hence, this project presents a mechanism of hand detection for computer graphical user interface control. The mechanism works on real time hand gestures. Through this project, computers’ GUI can be controlled using machine vision to help computer and laptop users to operate computer with ease without high costing. This project is driven by the increasing demand of computer and laptop users for an easier, low costing and portable GUI (Graphical User Interface) control. This design is to simplify HMI (Human Machine Interaction) by controlling the computers’ GUI with empty hands and only using the pre-installed web camera in the laptop as vision sensor. The methodology starts with image processing where batches of hand images were processed to detect the fingertips and the most minimum fingertip followed by video processing where real-time video were processed using the code from image processing. The image processing starts with image segmentation and background separation, centroid detection, fingertip detection and followed by movement detection. Video processing involves webcam start up and java robot programming to move the mouse cursor. When the programming is run, mouse cursor moves according to the hand movement in front of the camera. The outcome of this project is that the user could move mouse cursor by moving their hand in front of the webcam.